Identification of best practices for software outsourcing success in public sector organizations in Sri Lanka - Goonetilleke, Indika Udeni (My University, 2011)
Outsourcing has become common in today’s working environment. The software outsourcing plays a vital role in automation of the public services around the world. The area of this research is under-studied and published literature was not found in Sri Lanka. Public sector outsourcing projects are time consuming activities due to various reasons. Therefore the government officers have a very negative attitude on automation among the public organizations such as ministries, departments, statutory boards, authorities, commissions and public companies. Outsourcing organizations need to implement changes cautiously and evaluate their in-house capabilities. They also need to fully understand and apply the software outsourcing investment evaluation and benefits realization processes. In order to reach the degree of improvements, the Best Practices would be identified by this research. All these are to be done before and during the vendor/technology selection assessment and contract negotiation process. The data was collected from the survey of fourteen (14) organizations based on thirty (30) projects and two hundred and twelve (212) system users from the public sector organizations. The users were included from the all the categories of the organizations such as top, middle and junior staff members. The status of those projects include success, failure, partial failure and in developing stage. While doing the research several key issues were identified in outsourcing application software life cycle and those were discussed in the research too. The research has identified success, failure factors and software outsourcing success from the literature survey to design a conceptual model and introduced the Best Practices for the Sri Lankan context. The model was tested by identifying the relationship between success and prevention of failure factors with outsourcing success. This study will help the management and the Information Technology staff to identify the failure factors and take the necessary precautions using Best Practices. Hence, this study is timely and relevant for the public sector organizations in Sri Lanka as they are working towards the e-Government.